2021
DOI: 10.1093/ehjci/jeaa356.176
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of left atrial infiltration in cardiac transthyretin amyloidosis

Abstract: Funding Acknowledgements Type of funding sources: None. INTRODUCTION  The clinical significance of left atrial (LA) involvement in ATTR amyloidosis cardiomyopathy (ATTR-CM) has not been characterized. The aims of this study were to characterize: (1)LA pathology in explanted ATTR-CM hearts; (2)LA mechanics using echocardiographic speckle-tracking in a large cohort of ATTR-CM patients; (3)to study the association with mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…More work is needed in this area to identify ATTR‐CM patients without AF who are at higher risk of embolic events and who could benefit from close atrial thrombus/AF screening or early treatment with OAC. In this regard, identification of atrial dysfunction by strain echocardiography that has been found to be present in cardiac amyloidosis irrespectively of atrial cavity size, diastolic dysfunction and electrical atrial activity should be explored 21–23 . Unfortunately, atrial strain echocardiography data were not available in our cohort.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…More work is needed in this area to identify ATTR‐CM patients without AF who are at higher risk of embolic events and who could benefit from close atrial thrombus/AF screening or early treatment with OAC. In this regard, identification of atrial dysfunction by strain echocardiography that has been found to be present in cardiac amyloidosis irrespectively of atrial cavity size, diastolic dysfunction and electrical atrial activity should be explored 21–23 . Unfortunately, atrial strain echocardiography data were not available in our cohort.…”
Section: Discussionmentioning
confidence: 96%
“…In this regard, identification of atrial dysfunction by strain echocardiography that has been found to be present in cardiac amyloidosis irrespectively of atrial cavity size, diastolic dysfunction and electrical atrial activity should be explored. [21][22][23] Unfortunately, atrial strain echocardiography data were not available in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…(3) How does AU relate to abnormal atrial strain and increased atrial stiffness reported in patients with ATTR-CA? 27 (4) Does AU represent a modifiable substrate with ablation therapy? (5) Can medical therapy such as tafamadis known to stabilize ATTR-CA progression modify subsequent risk of incident AF?…”
Section: Discussionmentioning
confidence: 99%
“…99 Extensive atrial amyloid infiltration and consequently blunted atrial function have been recently described by Bandera et al with ATTR-CM revealed augmented atrial stiffness and all the three components of the atrial functioning (reservoir, conduit and contraction) were significantly impaired. 100 Furthermore, peak left atrial longitudinal strain was independently associated with the diagnosis of CA and, among patients with unexplained LVH, those with blunted peak left atrial longitudinal strain showed a eight-fold higher risk for CA beyond standard echocardiographic variables and cardiac biomarkers. 101 In a recent study performed in 13 tertiary Italian centers, the echocardiograms of patients aged 55 years performed during 15 days were collected (known CA or other cardiomyopathies with hypertrophic phenotype were excluded).…”
Section: Echocardiographymentioning
confidence: 93%